(Non-)Keynesian effects of fiscal austerity: New evidence from a large sample - António Afonso; José Alves; Florence Huart (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We empirically assess whether a usually expected negative response of private consumption and private investment to a fiscal consolidation is reversed. We focus on a large sample of 174 countries between 1970 and 2018. We also employ three alternative measures of the Cyclically Adjusted Primary Balance used to determine fiscal episodes: i) the IMF-WEO based; ii) the HP-based; and iii) the Hamilton (2018)-based. We find that: i) increases in government consumption have a Keynesian effect on real per capita private consumption; ii) there is a positive effect of tax increases on private consumption when there is a fiscal consolidation; iii) there is a crowding-in effect for private investment, from fiscal contractions. Moreover, expansionary fiscal consolidations occur particularly in highly indebted advanced economies following an increase in taxes. Finally, the negative effect of taxation on private consumption is larger when an economy is experiencing a financial crisis but it is not consolidating.
Keywords: C23; E21; E62; H5; H62; 330; non-Keynesian effects; fiscal consolidation; filtering; consumption; investment; financial crises; panel data; endogeneity